Access to fused tricyclic gamma-butyrolactones, a natural product -like scaffold - Kalmode, Hanuman P.; Handore, Kishor L.; Reddy, D. Srinivasa (Journal Of Organic Chemistry, 2017)
Serendipitous findings of an acid mediated skeletal rearrangement of bicydo-beta-ketoester having cyclopropyl ring to access fused tricyclic gamma-butyrolactones has been described. This novel transformation has been optimized to 30 mol% p-toluenesulfonic acid (p-TSA) in toluene using Dean Stark apparatus, where the aldol condensation, cyclopropyl ring opening followed by cyclization took place in a single-pot operation. The resulting tricyclic compounds are interesting chemotype with natural product resemblance and may find useful applications in the future.

Total synthesis and biological evaluation of cell adhesion inhibitors peribysin A and B: structural revision of peribysin B - Kalmode, Hanuman P.; Handore, Kishor L.; Rajput, Raveena; Shaikh, Samir R.; Gonnade, Rajesh G.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic letters, 2018)
Total synthesis of potent cell-adhesion inhibitors peribysins A and B has been accomplished for the first time in racemic form. A Diels-Alder/aldol sequence to build the skeleton and decoration of the desired functionalities of the targeted natural products using highly stereoselective operations are the highlights. The structures of synthesized peribysins were fully characterized using spectral data and single-crystal X-ray analysis. Through this total synthesis, the initially proposed structure of peribysin B has been revised. Furthermore, the cell-adhesion inhibition potential of the scaffold (two peribysins + three analogues) was confirmed using anti-adhesion assay.

Neural anti-inflammatory natural product periconianone A: total synthesis and biological evaluation - Kalmode, Hanuman P.; Patil, Suhag S.; Handore, Kishor L.; Athawale, Paresh R.; Dandela, Rambabu; Verma, Abhishek Kumar; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2019)
Total synthesis of periconianone A, an eremophilane-type sesquiterpenoid with impressive neural anti-inflammatory potential, has been accomplished. Diels-Alder/aldol strategy to construct tetrahydro-naphthalene-2,6-dione scaffold, allylic oxidation of dienone using DBU/O-2 and postulated biomimetic aldol reaction to construct 6/6/6 tricyclic system are the highlights of the present synthesis. Furthermore, the synthesized (+/-)-periconianone A and two close analogs were tested for their neural anti-inflammatory activity using various assays. In the course of our study we found a structurally simplified analog is superior to (+/-)-periconianone A.
Keywords: Aldol; Allylic oxidation; Biological evaluation; Cytotoxicity; Diels-Alder; Periconianone A

Overturning the peribysin family natural products isolated from periconia byssoides OUPS-N133: synthesis and stereochemical revision of peribysins A, B, C, F, and G - Athawale, Paresh R.; Kalmode, Hanuman P.; Motiwala, Zenia; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic Letters, 2020)
Herein we report the stereochemical revision of peribysins A, B, C, F, and G, guided by enantiospecific total synthesis starting from (+)-nootkatone. Furthermore, we reconfirmed the absolute stereochemistry of peribysin Q The highlights of the synthesis are enone transposition and kinetic iodination resulting in separation of diastereomers. Our findings coupled with synthetic and biological data previously reported by Danishefsky's group suggest that the original stereochemistries of peribysins A, B, C, F, and G were misassigned.

DBU/O-2-mediated oxidation of dienones - Athawale, Paresh R.; Kalmode, Hanuman P.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2021)
Herein, we describe a DBU/O-2-promoted novel method for oxidation of dienones to 2,6-dione derivatives. The reaction involves treatment of a dienone with DBU in acetonitrile employing molecular oxygen as the oxidant. Metal free conditions and an eco-friendly reagent are the striking features of this protocol. This transformation proceeds through a peroxide intermediate that upon Kornblum-DeLaMare rearrangement produces 2,6-diones. The method was successfully utilized for the synthesis of (+/-)-pleodendione with improved yields versus those of the traditional PDC-TBHP method.